2015
DOI: 10.1515/hsz-2014-0277
|View full text |Cite
|
Sign up to set email alerts
|

When core competence is not enough: functional interplay of the DEAD-box helicase core with ancillary domains and auxiliary factors in RNA binding and unwinding

Abstract: DEAD-box helicases catalyze RNA duplex unwinding in an ATP-dependent reaction. Members of the DEAD-box helicase family consist of a common helicase core formed by two RecA-like domains. According to the current mechanistic model for DEAD-box mediated RNA unwinding, binding of RNA and ATP triggers a conformational change of the helicase core, and leads to formation of a compact, closed state. In the closed conformation, the two parts of the active site for ATP hydrolysis and of the RNA binding site, residing on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 71 publications
(190 reference statements)
0
41
0
Order By: Relevance
“…ATP promotes high RNA-binding affinity by DEAD-box proteins [38]. The population effects seen in our smFRET studies suggest that Yra1 may decrease the affinity of Dbp2 for RNA, similar to the absence of ATP.…”
Section: Resultsmentioning
confidence: 85%
“…ATP promotes high RNA-binding affinity by DEAD-box proteins [38]. The population effects seen in our smFRET studies suggest that Yra1 may decrease the affinity of Dbp2 for RNA, similar to the absence of ATP.…”
Section: Resultsmentioning
confidence: 85%
“…DEAD‐box proteins, on the other hand, do not unwind in a translocation‐based fashion, but rather load directly onto the duplex region and separate the two strands (Q. Yang & Jankowsky, ; Yang, Del Campo, Lambowitz, & Jankowsky, ). This is possible because DEAD‐box proteins can disrupt RNA duplexes locally by bending one of the RNA strands (Rudolph & Klostermeier, ).…”
Section: General Biochemical Properties Of the Dead‐box Proteinsmentioning
confidence: 99%
“…Multiple X‐ray crystallographic studies of DEAD‐box helicases have demonstrated that DEAD‐box proteins contain a structurally conserved helicase core that consists of two globular RecA‐like domains (RecA_N and RecA_C) (Andersen et al, ; Del Campo & Lambowitz, ; Rudolph & Klostermeier, ; Sengoku, Nureki, Nakamura, Kobayashi, & Yokoyama, ; von Moeller, Basquin, & Conti, ). The two domains are connected by a flexible linker to form a characteristic “dumbbell‐like” core.…”
Section: General Biochemical Properties Of the Dead‐box Proteinsmentioning
confidence: 99%
“…RNA binding domains may anchor helicases on their target RNAs (18). Yet it is unknown if they act as passive anchors or actively present the bound RNA to the helicase core for unwinding (see (23)). Specifically, it has not been studied if these domains move with respect to the helicase core upon RNA binding, and how RNA binding to the ancillary domain may be communicated to the helicase core.…”
Section: Introductionmentioning
confidence: 99%